2022
DOI: 10.1111/ene.15543
|View full text |Cite
|
Sign up to set email alerts
|

Risk of future stroke in patients with a diagnosis of peripheral vertigo in the emergency department

Abstract: Vertigo is one of the most common symptoms of patients in the emergency department (ED), being reported in approximately 2.5%-4% of all ED patients [1,2]. Amongst the various neurological or nonneurological medical disorders causing vertigo, stroke is reported in approximately 3%-4% [3,4], but its prevalence could vary from 0.7% to 27% depending on the population studied [4-6]. Individualized risk assessment, detailed oculomotor examination and the progress of modern neuroimaging techniques have substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(77 reference statements)
4
1
0
Order By: Relevance
“…The risk was approximately 6 times higher at 7 days and gradually declined with increasing time from discharge. Similar results have been shown in several prior studies [ 11 , 20 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The risk was approximately 6 times higher at 7 days and gradually declined with increasing time from discharge. Similar results have been shown in several prior studies [ 11 , 20 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, an overemphasis on this approach may lead to a missed stroke diagnosis [ 36 , 37 ], posing a diagnostic challenge to ED physicians. This study, in line with previous ones [ 11 , 17 , 20 ], found that ED patients presenting with acute dizziness have a non-negligible risk of stroke even after being discharged from the ED without a stroke diagnosis. Several new observations that may extend current knowledge regarding this issue are discussed as follows.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations